AKSESIBILITAS JURU BAHASA ISYARAT (JBI) DALAM PRAKTIK IJAB QOBUL BAGI PENYANDANG DISABILITAS RUNGU PERSPEKTIF HUKUM ISLAM - Ahmad Nur Fadloli; Idarotul Nginayah (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
Ijab qobul is one of the pillars of marriage. The pronunciation must be done in one assembly, either directly or with a separation that does not cause the contract to be broken. The pronunciation of the ijab must use pronunciations that indicate the meaning of marriage and must be understood by the groom before expressing his consent to marriage. Judging from Islamic law, the translation of the pronunciation of the consent as previously explained is permissible and the marriage contract remains valid. Even if the translation is considered a "fashil" or separation of the marriage agreement, the separation is only a brief separation and does not result in the termination of the marriage contract. This research is library research. The data sources obtained include primary data and secondary data. Primary data sources come from the Al-Qur'an, Al-Qur'an tafsir books, hadith books, and fiqh books. Meanwhile, secondary data sources are taken from books, scientific journals, scientific articles and other sources related to the author's research object. It can be concluded that the accessibility of a sign language interpreter in the practice of ijab qobul between a bride with a hearing disability and her marriage guardian, reviewed according to Islamic law, is permissible and the marriage contract remains valid.